Thinking sociologically - Bauman, Zygmunt 1925-2017; May, Tim 1957- (Wiley-Blackwell, 2019)
In this book issues of climate change, sustainability, inequality, social justice, inclusion and the role of social media have risen to prominence, and we are collectively challenging our ways of thinking about intimacy, community, consumption, ethics, social identity, and more. This new third edition has been revised to reflect these and other transformations in our lives, helping us to think sociologically about the consequences of these burgeoning issues, how we organize our societies, understand ourselves and lead our lives.